2012
DOI: 10.1242/jeb.069799
|View full text |Cite
|
Sign up to set email alerts
|

Maximum metabolic rate, relative lift, wingbeat frequency, and stroke amplitude during tethered-flight in the adult locustLocusta migratoria

Abstract: . The modest flight metabolic rate of locusts is unlikely to be an artefact of individuals failing to exert themselves, because mean maximum lift was not significantly different from that required to support body mass (95±8%), mean wingbeat frequency was 23.7±0.6Hz, and mean stroke amplitude was 105±5deg in the forewing and 96±5deg in the hindwing -all of which are close to free-flight values. Instead, the low cost of flight could reflect the relatively small size and relatively modest anatomical power dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 68 publications
3
39
1
Order By: Relevance
“…There was also no significant difference between the body mass of adult locusts used in the present study and those used in earlier respirometry experiments (ANOVA, P0.21) (Snelling et al, 2011a;Snelling et al, 2012). Nevertheless, body-mass-specific values are presented (except for volume density, surface density and thickness estimates).…”
Section: Body Masscontrasting
confidence: 50%
See 4 more Smart Citations
“…There was also no significant difference between the body mass of adult locusts used in the present study and those used in earlier respirometry experiments (ANOVA, P0.21) (Snelling et al, 2011a;Snelling et al, 2012). Nevertheless, body-mass-specific values are presented (except for volume density, surface density and thickness estimates).…”
Section: Body Masscontrasting
confidence: 50%
“…The flight muscles contain predominantly fast phasic-type fibres (Kutsch and Usherwood, 1970;Mizisin and Ready, 1986;Wilson and Weis-Fogh, 1962), whereas the hopping muscles contain a mixture of fast phasic-type, slow tonic-type and intermediate-type fibres (Cochrane et al, 1972;Hoyle, 1978). Earlier respirometry revealed that the maximum oxygen consumption rate of adult hopping muscles during jumping exercise averages 158molh -1 g -1 body mass (Snelling et al, 2011a), whereas the flight muscle consumes a maximum of 967molh -1 g -1 during tethered-flight exercise (Snelling et al, 2012). According to the principles of symmorphosis, the 6.1-fold difference in aerobic capacity between the hopping and flight muscles should be matched by an equivalent difference in the overall volume, surface area and anatomical diffusing capacity of the tracheoles in the two muscles, and also in the total volume and inner membrane surface area of the mitochondria in the two muscles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations